Die Seele als ‚Zwischen‘ - Martina Bengert (Recherches Germaniques)
Simone Weil (1909-1943) read the Upanishads and the Bhagavadgîtâ with the similar intensity as she read Plato’s texts. In order to translate parts of these texts into French, she learned both Sanskrit and ancient Greek. Her Cahiers (18 notebooks of roughly 2000 pages) are not only a testimony of her work as a translator but more particularly of her attempt – inspired by various mystical experiences – at discovering the underlying relations between Christianity, Hinduism and the texts of Plato whom she considers to be a mystic and the founder of Early Christianity. Predominantly arranged in lists, her thinking constantly circles around the problem of how to read ‘adequately’, how to find true reading. On the basis of crucial notions of the Upanishads (i.a. ‚atman‘, ‚om‘ and ‚dharma‘) this paper will understand Weil’s “non-lecture” as an active-passive state of complete attention. It will show how in the Cahiers the soul is being written as a relational space by way of superimposing and intertwining different figures of thought and religious concepts. This space, which lies behind/underneath but more importantly in between the supposedly distinct, is a space that cannot be represented but still is present.